Expanding recognition and inclusion of animal-free organic agriculture in the sustainable agriculture movement - Seymour, Mona (Frontiers in Sustainable Food Systems, 2023)
Animal-free organic agriculture resides at the margins of sustainable agriculture discourse, practice, and imaginaries, which center animal-based forms of farming. However, the concerns and goals of sustainable agriculture are overwhelmingly consistent with those of many forms of animal-free organic agriculture (AFOA), described as organic farming sans animal production, labor, and byproducts. Despite this sidelining, AFOA has great potential to contribute to a more robust sustainable agriculture movement. In order to emphasize the continuities between animal-based and animal-free sustainable agriculture, this Perspective identifies a number of key similarities between animal-free and animal-based sustainable farming, including mutual foci on soil health and shared opposition to intensive animal agriculture. It contends that beyond being compatible with sustainable agriculture, AFOA holds answers to some of the difficult questions currently and potentially confronting animal-based agriculture, such as projected impacts of climate change on animal agriculture and stability of supply chains for animal-based soil amendments. Barriers to greater inclusion of AFOA into the sustainable agriculture movement exist as well; this piece suggests potential ways to address some of these challenges, including the integration of AFOA into formal sustainable agriculture education.